THE APPLICATION OF TECHNO ECOLOGY OF WATER SYSTEM AS AN EFFORT TO FULFILL WATER NEEDS OF AGRICULTURAL IRRIGATION FOR THE COMMUNITY OF WATER USE FARMERS ASSOCIATION (CASES IN INDONESIA) - SB, Basuki; Rahayu, Suparni S.; Suhartono, Edy; Hidayat, Wahyu Krisna (SAINSTEK, 2019)
ABSTRACT The general objective of the activity which involves the Application of Techno Ecology of the Water System as an Effort to Fulfill Water Needs of Agricultural Irrigation for the Community of Water User Farmer Association of Bumijawa District, Tegal Regency as an effort to meet the needs of agricultural irrigation water and facilitate the downstream process of Techno Ecology of the Water System resulting from community research. this can improve the quality and competitiveness of the Techno Ecology based Water Science and Technology system, establish and strengthen the network between technology makers of the Techno Ecology of the Water System and the technology users who have problems raising water from the river to meet the needs of agricultural irrigation water and improve the welfare of the community agricultural irrigation water users resulting from the Techno Ecology of the Water System. The specific target to be achieved is to disseminate the Techno Ecology of the Water System to get the technology to lift water from the river with a depth of approximately 20 meters below agricultural land. The method used is through several stages in the application of technology to the community by implementing together with partners identifying irrigation water needs by counseling, designing and calculating Appropriate technology (TTG) design drawings, making Appropriate technology (TTG), operational assistance by implementers in operating Appropriate technology (TTG) in a sustainable manner. Dissemination of technology to the community / partners by disseminating information on appropriate technology to the community through joint implementation with partners from the manufacturing process to the use of Appropriate technology (TTG). Work procedures to support the realization of the methods offered, counseling, equipment design and manufacturing, equipment work procedures, Appropriate technology (TTG) dissemination, assistance. Partner participation in the implementation of the establishment of an Institutional Forum, mapping of water distribution layouts, development of water distribution layouts, Design of water systems, the process of preparing work procedures, participating in the extension of water use / distribution in the Techno Ecology of Water Systems. The target of the Techno Ecological Equipment of the BEWRAM Water System and POLITIRTA Reservoir as an irrigation water reservoir so that farmers can increase the productivity of agricultural products. Keywords: Techno Ecology, BEWRAM Water System, POLITIRTA Reservoir, Agricultural Irrigation